The Influence of Return on Assets (ROA) and Return on Equity (ROE) on Stock Prices in Banking Companies on the Indonesia Stock Exchange for the 2023-2024 Period - Bernardus Sinurat; Aria Eka Agustina Abdullah; Musri'ah Musri'ah; Luqmanul Hakim; Muhammad Alkirom Wildan (International Journal of Economics and Management Research, 2025)
This study aims to evaluate the effect of Return on Assets (ROA) and Return on Equity (ROE) simultaneously on stock prices in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2023-2024. The data used is secondary data obtained from the financial statements of 47 banks, with a sample selection of 5 companies determined through purposive sampling method. The analysis was carried out with a quantitative approach and supported by SPSS version 25 software, through descriptive statistical testing, partial and simultaneous hypothesis testing, and regression model feasibility testing. The results show that both ROA and ROE have a positive and significant effect on stock prices, both individually and jointly. This finding confirms that profitability indicators have an important role in shaping investor perceptions and determining the market value of banking companies in Indonesia. Thus, the conclusions of this study support the utilization of a combination of these financial indicators as a basis for making investment decisions and corporate management strategies.